Exploring the construct of school readiness based on child development for kindergarten children - Farida Agus Setiawati; Rita Eka Izzaty; Agus Triyanto (REID (Research and Evaluation in Education), 2017)
Indonesian government has regulated that the basic age of readiness of a child to attend elementary schools is 7 years old. In fact, some children are not exactly 7 years old when they first go to school because they develop more rapidly. This study is aimed at investigating some aspects of child development which affect their readiness to attend elementary school. The subjects were 101 grade 1, 2, and 3 teachers of elementary schools in Yogyakarta, a special Region in Indonesia. The data were collected through interviews. The results of the data collection were analyzed using both descriptive quantitative and qualitative techniques. The results of the study show some aspects of child development affecting their readiness to attend elementary schools, including cognitive and language ability, social emotional skills, fine motor skills, gross motor skills, arts, religion and moral values, and some others. Beside these aspects, some problems in grades 1, 2, and 3 are also found. This study is expected to give significant indicators to create the construct of school readiness.